Sports and recreational activities - Mood, Dale P. (McGraw-Hill, 2003)
The purpose of the thirteenth edition of Sports and Recreational Activities is to provide current fundamental knowledge about a broad spectrum of physical activities. The physiological, psychological, and social benefits of participation in physical activities have long been proclaimed by physicians, physical educators, and recreation directors, and it appears that their advice is receiving the public's attention.